2012
DOI: 10.7585/kjps.2012.16.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Acetamiprid and Imidacloprid aerially applied to the Pine Forest

Abstract: Fate of acetamiprid and imidacloprid aerially sprayed to control pine wood nematode (Bursaphelenchus xylophilus) were studied in a forest of Haman area. Acetamiprid 20% SL or imidacloprid 20% DC were diluted 100 times and applied two times as rate of 50 L/ha using an aircraft of Bell 206 L helicopter. Average acetamiprid deposits on forest floor ranged from 2 to 4% of standard aerial application rate. Following to the second application, acetamiprid deposits in the pine needle ranged 1.8~8.5 mg/kg and then gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Several studies have been carried out on the control of MAH by aerial application 20–22 . In China, aerial application of insecticides to MAH was adopted as early as 1984, but then the research stagnated for the next 30 years and only gradually re‐emerged in 2011 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been carried out on the control of MAH by aerial application 20–22 . In China, aerial application of insecticides to MAH was adopted as early as 1984, but then the research stagnated for the next 30 years and only gradually re‐emerged in 2011 23 .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Several studies have been carried out on the control of MAH by aerial application. [20][21][22] In China, aerial application of insecticides to MAH was adopted as early as 1984, but then the research stagnated for the next 30 years and only gradually re-emerged in 2011. 23 A study by Yao et al 24 revealed that the aerial spraying of biocontrol bacteria as an alternative to the surface pathogenic bacteria of pine wood nematodes required a 48-h rain-free period.…”
Section: Introductionmentioning
confidence: 99%